Financial environment and business development : proceedings of the 16th Eurasia Business and Economics Society Conference - Bilgin, Mehmet Huseyin; Danis, Hakan; Demir, Ender; Can, Ugur (Springer, 2016)
This volume focuses on the latest findings concerning financial environment research and the effects on business. Major topics addressed range from finance-driven globalization, contagion risk transmission, financial sustainability, and bank efficiency, to oil price shocks and spot prices research. Further topics include family business, business valuation, public sector development and business organization in the globalized environment. This book features selected peer-reviewed articles from the 16th EBES conference in Istanbul, where over 270 papers were presented by 478 researchers from 56 countries.
Keywords: Economics -- Congresses.; Business -- Congresses.; Finance -- Congresses.; elektronické knihy; electronic books